2011
DOI: 10.1016/j.pnpbp.2010.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Antipsychotic dose and diminished neural modulation: A multi-site fMRI study

Abstract: Background-The effect of antipsychotics on the blood oxygen level dependent signal in schizophrenia is poorly understood. The purpose of the present investigation is to examine the effect of type (typical or atypical) and dose of antipsychotic medication on independent neural networks during a motor task in a large, multi-site functional magnetic resonance imaging investigation.Methods-Seventy-nine medicated patients with schizophrenia and 114 comparison subjects from the Mind Clinical Imaging Consortium datab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 57 publications
(69 reference statements)
0
31
2
Order By: Relevance
“…The studies on rTMS treatment for negative symptoms of schizophrenia are conducted among medicated patients. Antipsychotics cause dopamine antagonism at the D2 receptor, and there is evidence that antipsychotics diminish neural activation in motor and default mode network in patients with schizophrenia (Abbott et al, 2011). In addition, there is evidence for reduced inhibition, impaired connectivity and reduced plasticity in both medicated and unmedicated patients with schizophrenia in all stages of the illness.…”
Section: Discussionmentioning
confidence: 99%
“…The studies on rTMS treatment for negative symptoms of schizophrenia are conducted among medicated patients. Antipsychotics cause dopamine antagonism at the D2 receptor, and there is evidence that antipsychotics diminish neural activation in motor and default mode network in patients with schizophrenia (Abbott et al, 2011). In addition, there is evidence for reduced inhibition, impaired connectivity and reduced plasticity in both medicated and unmedicated patients with schizophrenia in all stages of the illness.…”
Section: Discussionmentioning
confidence: 99%
“…Dose year of antipsychotics were calculated using the formula described by Abbott et al, 2011: Dose0.16667emyear=false[false(dosefalse(mgfalse)100CPZfalse)/drugequivalentfalse]false[daysondose/365.25false]false[1year/false(100CPZ1yearfalse)false]…”
Section: Methodsmentioning
confidence: 99%
“…Using PET, Tomasi et al (91) reported a negative correlation between dopamine transporter availability and DMN deactivation during an attention task, suggesting that dopamine release may reduce DMN activity. The most direct link between DMN function and dopaminergic function comes from the observation that conventional antipsychotic medications, which act via dopaminergic antagonism, show a dose-dependent correlation with DMN activity in schizophrenia patients (92). …”
Section: Default Mode Networkmentioning
confidence: 99%